2015
DOI: 10.1080/03650340.2015.1072623
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate contents in some vegetables in Tunisia

Abstract: This study reports the nitrate level of 22 vegetables species collected from 40 farms in several locations of an intensive agricultural area in two regions of Tunisia (Sousse and Monastir). Nitrate levels ranged between 57 and 2970 mg kg -1 . The highest and the lowest levels were found in turnip and tomato, respectively. Only five species (potato, field bean, cauliflower, pea and artichoke) had exceeded the norms established by the World Health Organization. Factors influencing nitrate accumulation in some ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The range between 100 and 150 kg N ha −1 is recommended for the species to meet yield level, production cost, and leaf quality, allowing to keep low nitrate content below safe limits and avoid a negative impact on leaf nutritional value. In a survey study on nitrate content of 22 vegetable species produced in Tunisia under organic and conventional farming systems [12], significant differences were observed in Swiss chard nitrate content (1176 vs. 2243 mg kg −1 fresh weight-Fw, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…The range between 100 and 150 kg N ha −1 is recommended for the species to meet yield level, production cost, and leaf quality, allowing to keep low nitrate content below safe limits and avoid a negative impact on leaf nutritional value. In a survey study on nitrate content of 22 vegetable species produced in Tunisia under organic and conventional farming systems [12], significant differences were observed in Swiss chard nitrate content (1176 vs. 2243 mg kg −1 fresh weight-Fw, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…However, Swiss chard is among the leafy vegetables accumulating excessive nitrate amount, with over 60% in the petiole [15][16][17]. Several studies [18,19] showed that high N fertilization levels negatively affect the quality of Swiss chard leaves, instead Razgallah et al [20] found lower nitrate content in organically than conventionally cultivated Swiss chard. In this context, the application of organic amendments to Swiss chard cultivation, could be a way to reduce or even replace the inorganic fertilization, while assuring plant nutrition, crop yield, and quality.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of high nitrate content in vegetables, fruits, meat, and dairy products is relevant for scientists in different countries [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%